Extent of Capital Flight and Its Impact on Economic Growth: The Case of WAEMU countries - Kuamvi Sodji (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
This paper estimates the magnitude of capital flight and analyzes its impact on economic growth in the West African Economic and Monetary Union countries. Over the period from 1970 to 2019, total real capital flight from these countries is positive and significant with a magnitude that amounts to $31,075.26 million in constant dollars, or 17.40 percent of investment. Six countries have experienced significant real capital flight over the past four decades: Ivory Coast, Guinea Bissau, Mali, Niger, Burkina Faso, and Senegal. Using dynamic fixed-effects estimation, the paper finds that, in the long run, capital flight significantly reduces economic growth in countries where capital flight is positive and that the negative effect does not appear to be cumulative with investment in the case of these groups of countries. In addition, the paper recommends that the authorities commit to reducing capital flight by improving governance and strengthening the quality of institutions.